2011
DOI: 10.1029/2009pa001923
|View full text |Cite
|
Sign up to set email alerts
|

Productivity collapses in the Arabian Sea during glacial cold phases

Abstract: [1] Productivity in the Arabian Sea is one of the highest in the world. It is controlled by seasonally reversing monsoonal wind-driven upwelling of nutrient-rich deeper waters which fuel phytoplankton growth. The detailed history of upwelling-induced productivity in the eastern Arabian Sea is unknown. Here we present paleoproductivity records from a composite sediment core at the millennial scale during the last 80 kyr B.P. These records are based on relative abundance counts of planktonic foraminifera and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 57 publications
5
97
1
Order By: Relevance
“…This includes the most recent climate changes from the Medieval Warm Period and the Little Ice Age. The analysis of proxy paleo-records also suggests a strong coupling between northern climate excursions and changes in productivity and denitrification in the Arabian Sea at different timescales (e.g., Altabet et al, 1995Altabet et al, , 1999Altabet et al, , 2002Gupta et al, 2003;Singh et al, 2011). For instance, Altabet et al (1999) found that denitrification was greatest during interglacial periods and was probably not active during most glacial phases.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the most recent climate changes from the Medieval Warm Period and the Little Ice Age. The analysis of proxy paleo-records also suggests a strong coupling between northern climate excursions and changes in productivity and denitrification in the Arabian Sea at different timescales (e.g., Altabet et al, 1995Altabet et al, , 1999Altabet et al, , 2002Gupta et al, 2003;Singh et al, 2011). For instance, Altabet et al (1999) found that denitrification was greatest during interglacial periods and was probably not active during most glacial phases.…”
Section: Introductionmentioning
confidence: 99%
“…The net decline in export production observed in this study was dominated by the decline in tropical and subtropical waters. Many palaeoproductivity studies located outside of the subantarctic zone have found weakened productivity at the LGM (Chang et al, 2014(Chang et al, , 2015Costa et al, 2016;Crusius et al, 2004;Kohfeld et al, 2005;Kohfeld and Chase, 2011;Jaccard et al, 2005;McKay et al, 2015;Ortiz et al, 2004;Riethdorf et al, 2013;Salvatteci et al, 2016;Singh et al, 2011;Thomas et al, 1995). Additionally, an enhanced utilisation of available nutrients in the subantarctic zone would reduce the nutrient content of intermediate waters formed in the Southern Ocean and would thus reduce the delivery of nutrients to lower latitudes (Sarmiento et al, 2004).…”
Section: Reconciling Export Productionmentioning
confidence: 99%
“…The affected regions include waters south of the Antarctic Polar Front (Francois et al, 1997;Jaccard et al, 2013), the North Pacific (Crusius et al, 2004;Jaccard et al, 2005;Kohfeld and Chase, 2011;Ortiz et al, 2004), the tropical Indian Ocean (Singh et al, 2011) and the equatorial Pacific (Costa et al, 2016;Herguera, 2000;Loubere et al, 2007). A weaker export production in these regions would have offset a strengthened biological pump in the subantarctic, thereby weakening the ability of the ocean to store carbon during glacial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Progress is also being made in understanding winter monsoon and summer monsoon linkages at the millennial timescale. For example, recent work offshore Goa, western India, shows synchronous breakdown in summer and winter monsoon airflow over the Arabian Sea during Heinrich events (Singh et al, 2011), which is in contrast to the East Asian Monsoon system that shows an asynchronous relationship between summer and winter monsoon strength at the millennial scale (Yancheva et al, 2007).…”
Section: Background Motivation For Drilling In the Bay Of Bengalmentioning
confidence: 99%